Being/longing: visualizing belonging with Palestinian refugee children. (28th May 2023) - Marshall, David J.
ABSTRACT: Rejecting theorizations of refugee camps as humanitarian spaces of exception and bare life, recent research has emphasized how camps are sites of material struggle, and how refugees are agential political subjects. While valuable, this research bifurcates between the material dwellings of refugee camps on one hand and the political subjectivity of refugees on the other. In contrast, this paper examines how Palestinian refugees reproduce a sense of collective belonging within the physical space of the camp and through material practices of care. This research centers the voices of Palestinian children to understand how they view their inherited refugee identities in the context of multi-generational displacement. Using participatory digital storytelling, this research illustrates how, for some Palestinian refugee children, a sense of longing for a future return to their past homeland motivates acts of care in the present that produces a sense of belonging in the camp. The creative agency that refugee youth demonstrate in articulating this entangled temporality of belonging challenges top-down models of youth socialization and refugee subjectivity. The importance of visual and narrative practices in reproducing refugee-ness suggests a wider role for creative methods in research with refugees. This paper introduces place-based digital storytelling as one such method.